Altered Ecologies Fire, climate and human influence on terrestrial landscapes - Haberle, S.; Stevenson, J.; Prebble, M. (Terra Australis, 2010)
Like a star chart this volume orientates the reader to the key issues and debates in Pacific and Australasian biogeography, palaeoecology and human ecology. A feature of this collection is the diversity of approaches ranging from interpretation of the biogeographic significance of plant and animal distributional patterns, pollen analysis from peats and lake sediments to discern Quaternary climate change, explanation of the patterns of faunal extinction events, the interplay of fire on landscape evolution, and models of the environmental consequences of human settlement patterns. The diversity of approaches, geographic scope and academic rigor are a fitting tribute to the enormous contributions of Geoff Hope. As made apparent in this volume, Hope pioneered multidisciplinary understanding of the history and impacts of human cultures in the Australia- Pacific region, arguably the globe's premier model systems for understanding the consequences of human colonization on ecological systems. The distinguished scholars who have contributed to this volume also demonstrate Hope's enduring contribution as an inspirational research leader, collaborator and mentor. Terra Australis leave no doubt that history matters, not only for land management, but more importantly, in alerting settler and indigenous societies alike to their past ecological impacts and future environmental trajectories.